Sexually transmitted infection testing awareness, uptake and diagnosis among urban refugee and displaced youth living in informal settlements in Kampala, Uganda: a cross-sectional study. Issue 3 (23rd December 2019) - Logie, Carmen Helen; Okumu, Moses; Mwima, Simon; Kyambadde, Peter; Hakiza, Robert; Kibathi, Irungu Peter; Kironde, Emmanuel
Abstract : Background: Sexually transmitted infection (STI) prevention needs among urban refugee and displaced youth are understudied. The study objective was to explore factors associated with the STI prevention cascade (STI services awareness, testing, diagnosis) among urban refugee and displaced youth in Kampala, Uganda. Methods: We implemented a cross-sectional survey with youth aged 16–24 years in informal settlements in Kampala. We conducted bivariate and multivariable logistic regression analyses to identify social ecological (intrapersonal, interpersonal, community) level factors associated with STI testing services awareness, lifetime STI testing, and lifetime STI diagnosis. Results: Participants (n=445; mean age 19.3, SD 2.6, years) included young women (n=333, 74.8%) and young men (n=112, 25.2%). Less than half (43.8%) were aware of community STI services. One-quarter (26.1%) reported lifetime STI testing. Of these, 39.5% reported a lifetime STI diagnosis. In multivariable analyses among young women, age, lifetime sex partners, and lower adolescent sexual and reproductive health (SRH)-related stigma were associated with STI services awareness; and age, lower adolescent SRH-related stigma, and food security were associated with STI testing. Among young men, time in Uganda and lower HIV-related stigma were associated with STI services awareness; and age, condom self-efficacy, and increased adolescent SRH-related stigma were associated with testing. Lifetime sex partners, lower condom self-efficacy, and lower adolescent SRH-related stigma were associated with lifetime STI diagnosis. Conclusions: Social ecological factors including stigma (adolescent SRH-related, HIV-related) were associated with STI testing and diagnosis among young urban refugees. Gender, age and stigma-tailored strategies can advance the STI prevention cascade among urban young refugees.